ONGs e suas parcerias: relações e influências - Silva, Jamille Coelho da (2012)
This study represents the analysis of the types of partnerships undertaken by NonGovernmental Organizations (NGOs) and their influences stemming from this relationship. It houses the historical context of the emergence of NGOs, concepts that permeate these types of organizations, legal aspects governing the existing third sector organizations, including how they were related to the Civil Code and the Law 9.790/99, considered the law of the sector. Contains relations between NGOs and Government, NGOs and companies, and NGOs and the like. There is also discussion on the influence of these institutional relationships to the organizational structure of NGOs expose the end will be a story to illustrate empirically the consequences of relations within a specific NGO: NGO to reintegrate. The complex networks of relationships made by an NGO brings some benefits in terms of growth and improvement in quality of care of their social demands. Demonstrating is how complex is this large network of relationships.